2009
DOI: 10.1002/erv.938
|View full text |Cite
|
Sign up to set email alerts
|

Personality dimensions among women with an eating disorder: Towards reconceptualizing DSM

Abstract: A flexible approach to diagnosis, which includes personality dimensions along with a description of eating disorder symptoms, may result in a more inclusive and useful diagnostic scheme for treating women with eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
(55 reference statements)
6
37
0
Order By: Relevance
“…Moreover, the proportion of AN diagnoses did not moderate the effect size for this domain, which is consistent with previous studies conducted in samples of all ages that reported that individuals with AN-R, AN-BP, and BN consistently reported lower levels of extraversion than non-ED controls (Farstad et al, 2016;Tasca et al, 2009). The fact that adolescents with EDs are more inhibited and suspicious in relationships, despite relational needs, could make them more vulnerable to eating control/compulsion and body image concerns in order to fulfill these relational needs, thus highlighting the intrinsic relationship between personality and ED symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the proportion of AN diagnoses did not moderate the effect size for this domain, which is consistent with previous studies conducted in samples of all ages that reported that individuals with AN-R, AN-BP, and BN consistently reported lower levels of extraversion than non-ED controls (Farstad et al, 2016;Tasca et al, 2009). The fact that adolescents with EDs are more inhibited and suspicious in relationships, despite relational needs, could make them more vulnerable to eating control/compulsion and body image concerns in order to fulfill these relational needs, thus highlighting the intrinsic relationship between personality and ED symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…It is also possible that conscientiousness affects body weight through eating behavior. For example, conscientious individuals are less likely to show eating disorders (e.g., anorexia, bulimia, and binge eating disorder) (Brannan and Petrie, 2008; Tasca et al, 2009). Moreover, conscientious individuals tend to maintain a relatively high level of cognitive dietary restraint (i.e., conscious control of food intake with concerns about shape and weight) (Provencher et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of studies investigating the FFM dimensions among eating disorders has found profiles of high neuroticism, low extraversion, low agreeableness, and low conscientiousness [12][13][14]. De Bolle and colleagues [14] compared anorexia nervosa restricting (AN-R), anorexia nervosa binge/purging, and bulimic inpatients on FFM traits.…”
Section: Eating Disorders and Personality Traitsmentioning
confidence: 97%